Sense and Sensibility - Austen, Jane (London Harper Perss, 2010)
When two sisters appear to be deserted by the young men they had intended to marry, the stage is set for a delicious comedy of manners that not only showcases Austen's perception, humor and incomparable prose, but offers a splendid glimpse of upper and middle-class English society of the early 19th century.
Keywords: Young women -- Manners and customs -- England